A method for preparing positive electrode material of lithium ion battery

By surface modification of LiNi0.6Mn0.4O2, a gradient distribution of cobalt element is formed, which solves the problems of low capacity and poor rate performance of cobalt-free positive electrode materials, and realizes the positive electrode materials of lithium-ion batteries with good capacity and circulation performance.

CN115991504BActive Publication Date: 2025-02-07HUNAN JAPRUI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211474919.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-23
Publication Date
2025-02-07
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

The existing cobalt-free cathode material LiNi0.6Mn0.4O2 has low capacity and poor rate performance due to large polarization resistance.

Method used

A relatively simple preparation method is used to surface modify LiNi0.6Mn0.4O2, by mixing polyvinylpyrrolidone, LiNi0.6Mn0.4O2 and cobalt nitrate in a specific ratio and sintering at high temperature to form cobalt elements in crystal grains. The surface to interior gradient distribution.

Benefits of technology

The electrochemical properties of the modified cathode material include capacity and cycle stability, while reducing battery costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115991504B_ABST
    Figure CN115991504B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps: 0.6 Mn 0.4 The (OH)2 precursor is mixed with lithium carbonate and then ground and sintered to obtain LiNi 0.6 Mn 0.4 O2; using anhydrous ethanol as solvent, polyvinyl pyrrolidone, prepared LiNi 0.6 Mn 0.4 O2 and cobalt nitrate are mixed and stirred until the ethanol evaporates naturally; the mixed material is sintered at 500℃~600℃ for 3~7h to obtain surface-modified LiNi 0.6 Mn 0.4 O2, and the lithium-ion battery positive electrode material is obtained. The present invention adopts a relatively simple preparation method to prepare the low-cost cobalt-free positive electrode material LiNi 0.6 Mn 0.4 O2 is used for surface modification to produce positive electrode materials with high capacity and good cycle performance. The electrochemical performance of the obtained materials is greatly improved and has great practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a positive electrode material for a lithium ion battery. Background Art

[0002] With the rapid popularization of electric vehicles, the demand for lithium-ion batteries as an important power source has greatly increased. The positive electrode is the most critical and costly part of lithium-ion batteries. In recent years, the supply of positive electrode materials has been repeatedly challenged. As the most expensive element, the price of cobalt has been rising year by year, and people have to find ways to reduce the amount of cobalt used.

[0003] Yang-Kook Sun et al. synthesized LiNi by coprecipitation method. 1-x Mn x For binary materials such as LiNiO2 (0.1≤x≤0.5), it was found that the capacity increases with the increase of Ni content, but the cycle stability decreases. 0.6 Co 0.4 O2 (referred to as NC64), LiNi 0.6 Mn 0.4 O2 (abbreviated as NM64), LiNi 0.6 Co 0.2 Mn 0.2 A systematic study was conducted on three positive electrode materials, including O2 (NCM622 for short), and it was found that although the cobalt element plays an important role in improving the rate performance (i.e. fast charging and discharging), it is not conducive to the cycle stability of the battery, which is more prominent under high voltage.

[0004] Although LiNi 0.6 Mn 0.4 O2 (referred to as NM64) compared to LiNi 0.6 Co 0.2 Mn 0.2 O2 (referred to as NCM622) has higher stability, but due to the poor conductivity of the material itself, the capacity is much lower than that of NCM622 at the same nickel content. 0.6 Mn 0.4 On the premise of maintaining the stability of O2 (NM64 for short), it can also improve its capacity, which will have great practical application significance. Summary of the invention

[0005] The present invention aims to provide a method for preparing a positive electrode material for a lithium-ion battery, so as to solve the problem of existing cobalt-free positive electrode materials LiNi 0.6 Mn 0.4O2 has problems such as low capacity and poor rate performance due to its large polarization resistance. The present invention adopts a relatively simple preparation method to prepare the low-cost cobalt-free positive electrode material LiNi 0.6 Mn 0.4 O2 is used for surface modification, and the electrochemical performance of the modified positive electrode material is greatly improved, which has great practical value and broad market prospects.

[0006] To achieve the above object, the present invention provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0007] Step 1: Ni 0.6 Mn 0.4 The (OH)2 precursor is mixed with lithium carbonate and then ground and sintered to obtain LiNi 0.6 Mn 0.4 O2;

[0008] Step 2: Using anhydrous ethanol as solvent, polyvinyl pyrrolidone and the LiNi prepared in step 1 are reacted with 0.6 Mn 0.4 Mix O2 and cobalt nitrate and stir until the ethanol evaporates naturally;

[0009] Step 3: Sinter the material obtained in step 2 at 500°C to 600°C for 3 to 7 hours to obtain surface-modified LiNi 0.6 Mn 0.4 O2, thus obtaining the positive electrode material for a lithium-ion battery; the cobalt content in the grains of the positive electrode material for a lithium-ion battery gradually decreases from the surface to the inside, showing a gradient distribution;

[0010] Wherein, in step 2, polyvinyl pyrrolidone and LiNi prepared in step 1 0.6 Mn 0.4 The mass ratio of O2 and cobalt nitrate is 2:1:0.005-0.03.

[0011] Furthermore, in step 1, Ni 0.6 Mn 0.4 The molar ratio of (OH)2 precursor to lithium carbonate is 2:1.05.

[0012] Furthermore, in step 1, the sintering temperature is 500° C. to 850° C., and the sintering time is 10 to 20 hours.

[0013] Furthermore, in step 2, the molecular weight of polyvinyl pyrrolidone is 40,000 to 100,000.

[0014] Further, in step 2, according to the synthetic mass percentage of 0.5% cobalt tetroxide, polyvinyl pyrrolidone, LiNi prepared in step 1 0.6 Mn 0.4The mass ratio of O2 to cobalt nitrate is 2:1:0.018.

[0015] Furthermore, in Step 2, the dosage of absolute ethanol is 80 - 120 times the mass of polyvinylpyrrolidone.

[0016] Furthermore, the sintering treatments in Step 1 and Step 3 are both carried out in an air atmosphere.

[0017] The present invention has the following beneficial effects:

[0018] 1. The present invention provides a preparation method for a cathode material of a lithium-ion battery. By using a relatively simple preparation method to modify the surface of the low-cost cobalt-free cathode material LiNi 0.6 Mn 0.4 O2, a cathode material with high capacity and good cycling performance is obtained. At the same time, due to the avoidance of the large-scale use of cobalt elements, the battery cost is greatly reduced.

[0019] 2. The present invention provides a preparation method for a cathode material of a lithium-ion battery. By using the polymer polyvinylpyrrolidone as an adjuvant, the surface can be modified very uniformly. After re-sintering, polyvinylpyrrolidone decomposes and volatilizes, having no influence on the material. At the same time, during the high-temperature sintering process, cobalt nitrate is transformed into cobalt tetroxide, and cobalt tetroxide can react with the residual lithium source on the surface of LiNi 0.6 Mn 0.4 O2, reconstructing the surface of LiNi 0.6 Mn 0.4 O2, so that the Co element shows a gradient distribution within a range of 200 nm from the surface to the interior of the LiNi 0.6 Mn 0.4 O2 crystal grains. In this way, the surface of the modified material (abbreviated as Co-NM64, that is, the cathode material of the lithium-ion battery prepared by the present invention) becomes LiNi 1-x-y Co x Mn y O2 (where 0 < x < 1, 0 < y < 1, and x gradually decreases from the surface to the interior). Since a large part of the battery resistance comes from the interface, reducing the interface resistance can significantly reduce the polarization of the battery, thereby improving the battery capacity. During the modified sintering process, the residual lithium source that hinders the lithium-ion transmission is consumed, and the cobalt element has good electrical conductivity. Therefore, the surface conductivity of the modified material is greatly improved, the resistance is significantly reduced, and the capacity is thus greatly increased.

[0020] It should be noted that although the cobalt element can improve the electrical conductivity of the battery material, when it exists in the material body, it is not conducive to the cycling stability of the battery. Co-NM64 and LiNi 0.6 Mn 0.4Compared with O2, not only the surface conductivity is improved, but also the bulk structure is not changed, which not only improves the capacity but also maintains the cycle stability. The specific principle is as follows: (a) a small amount of cobalt nitrate is used to treat LiNi 0.6 Mn 0.4 Surface modification with O2 can significantly reduce the polarization of the battery, thereby greatly improving the battery capacity and rate performance. Surface modification with other elements does not have such advantages.

[0021] (b) Using polyvinyl pyrrolidone to assist in coating can make cobalt nitrate evenly covered on LiNi 0.6 Mn 0.4 O2 surface.

[0022] (c) LiNi prepared in step 1 0.6 Mn 0.4 The mass ratio of O2 and cobalt nitrate is 1:0.005-0.03, which can effectively improve the performance of LiNi 0.6 Mn 0.4 O2 surface. Too low a cobalt mass ratio cannot effectively modify the positive electrode material, and too high a mass ratio is not conducive to the formation of a good lithium ion conductor LiNi 1-x-y Co x Mn y O2, thereby hindering the transmission of lithium ions, increasing polarization and reducing battery capacity; at the same time, the cost will increase due to the large amount of cobalt used.

[0023] (d) LiNi 0.6 Mn 0.4 O2 is re-sintered, and cobalt nitrate is converted into cobalt tetroxide. After cobalt tetroxide reacts with the residual lithium source on the surface that hinders the transmission of lithium ions, the original cobalt tetroxide coating is converted into a gradient-distributed LiNi 1-x-y Co x Mn y O2 not only improves the LiNi 0.6 Mn 0.4 The conductivity of O2 makes the surface modification layer more compatible, combining the advantages of coating and doping. Because when the sintering temperature is too low, cobalt tetroxide is not enough to fully react with the residual lithium source to form a gradient distribution of LiNi 1-x-y Co x Mn y O2, the conductivity will also decrease, and even polyvinyl pyrrolidone cannot be completely decomposed; if the sintering temperature is too high, the internal defects of the material will increase significantly and the performance will be significantly reduced.

[0024] 3. The lithium-ion battery positive electrode material Co-NM64 prepared by the method of the present invention and the existing commercial LiNi 0.6 Co 0.2 Mn0.2 Compared with O2 (NCM622) positive electrode material, it not only has comparable capacity but also has higher cycle stability. At the same time, it is also more cost-effective due to the reduction in the use of expensive cobalt elements.

[0025] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0027] Figure 1 It uses LiNi 0.6 Mn 0.4 O2 (referred to as NM64), the surface modified material prepared in Example 1 (referred to as Co-NM64) and commercial LiNi 0.6 Co 0.2 Mn 0.2 Cycling performance diagram of batteries assembled with O2 (referred to as NCM622) positive electrode materials;

[0028] Figure 2 It is a cycle performance diagram of batteries assembled with positive electrode materials prepared using NM64, Example 1 and Comparative Examples 1-5;

[0029] FIG3( a ) is a slice diagram of the positive electrode material particles prepared in Example 1 taken from the material particles by focused ion beam (FIB), which corresponds to the surface and the interior of the material from top to bottom;

[0030] Figure 3(b) is the Co element distribution diagram inside the Co-NM64 grain corresponding to Figure 3(a);

[0031] Figure 4 It is a curve diagram of the change in the content of the three elements nickel, cobalt and manganese from the surface to the inside of the Co-NM64 grain along the arrow in Figure 3(b). DETAILED DESCRIPTION

[0032] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0033] Embodiment 1:

[0034] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0035] (1) Commercially available Ni 0.6 Mn 0.4(OH)2 precursor and battery-grade lithium carbonate are mixed evenly at a molar ratio of 2:1.05 and ground for half an hour;

[0036] (2) The ground material is sintered at 500 °C to 850 °C for 10 to 20 h to obtain LiNi 0.6 Mn 0.4 O2;

[0037] (3) Calculated according to the synthetic mass percentage of 0.5% cobalt tetroxide, polyvinylpyrrolidone (PVP, molecular weight 40000 - 100000), LiNi 0.6 Mn 0.4 O2 and cobalt nitrate are mixed at a mass ratio of 2:1:0.018, and absolute ethanol with a mass 100 times that of PVP is used as the solvent, and stirred until the ethanol naturally evaporates to dryness;

[0038] (4) The mixed material obtained in step (3) is sintered at 550 °C for 4 to 5 h to obtain a lithium-ion battery cathode material, denoted as Co-NM64. Finally, the surface of the lithium-ion battery cathode material becomes LiNi 1-x-y Co x Mn y O2 (where 0 < x < 1, 0 < y < 1, and x gradually decreases from the surface to the inside).

[0039] Example 2:

[0040] A preparation method of a lithium-ion battery cathode material, comprising the following steps:

[0041] (1) The commercially available Ni 0.6 Mn 0.4 (OH)2 precursor and battery-grade lithium carbonate are mixed evenly at a molar ratio of 2:1 and ground for half an hour;

[0042] (2) The ground material is sintered at 500 °C to 850 °C for 10 to 20 h to obtain LiNi 0.6 Mn 0.4 O2;

[0043] (3) Polyvinylpyrrolidone (PVP, molecular weight 40000 - 100000), LiNi 0.6 Mn 0.4 O2 and cobalt nitrate are mixed at a mass ratio of 2:1:0.005, and absolute ethanol with a mass 100 times that of PVP is used as the solvent, and stirred until the ethanol naturally evaporates to dryness;

[0044] (4) The mixed material obtained in step (3) is sintered at 500 °C for 4 to 5 h to obtain a lithium-ion battery cathode material, denoted as Co-NM64-1.

[0045] Example 3:

[0046] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0047] (1) Commercially available Ni 0.6 Mn 0.4 The (OH)2 precursor and battery-grade lithium carbonate were mixed evenly in a molar ratio of 2:1.2 and ground for half an hour;

[0048] (2) The ground material is sintered at 500°C to 850°C for 10 to 20 hours to obtain LiNi 0.6 Mn 0.4 O2;

[0049] (3) Polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and cobalt nitrate are mixed in a mass ratio of 2:1:0.03, and anhydrous ethanol with a mass of 100 times that of PVP is used as a solvent, and stirred until the ethanol evaporates naturally;

[0050] (4) The mixed material obtained in step (3) is sintered at 600° C. for 4 to 5 hours to obtain a lithium-ion battery positive electrode material, which is recorded as Co-NM64-2.

[0051] Comparative Example 1: (Modification with zinc nitrate)

[0052] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0053] (1) Commercially available Ni 0.6 Mn 0.4 The (OH)2 precursor and battery-grade lithium carbonate were mixed evenly in a molar ratio of 2:1.05 and ground for half an hour;

[0054] (2) The ground material is sintered at 500°C to 850°C for 10 to 20 hours to obtain LiNi 0.6 Mn 0.4 O2;

[0055] (3) Using anhydrous ethanol as solvent, polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and zinc nitrate are mixed in a mass ratio of 2:1:0.018, and stirred until the ethanol evaporates naturally;

[0056] (4) Sinter the material obtained in the previous step at 500°C to 600°C for 3 to 7 hours to obtain modified LiNi 0.6 Mn 0.4O2 positive electrode material, denoted as Zn-NM64.

[0057] Comparative Example 2: (Modification with aluminum nitrate)

[0058] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0059] (1) Commercially available Ni 0.6 Mn 0.4 The (OH)2 precursor and battery-grade lithium carbonate were mixed evenly in a molar ratio of 2:1.05 and ground for half an hour;

[0060] (2) The ground material is sintered at 500°C to 850°C for 10 to 20 hours to obtain LiNi 0.6 Mn 0.4 O2;

[0061] (3) Using anhydrous ethanol as the solvent, polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and aluminum nitrate are mixed in a mass ratio of 2:1:0.037, and stirred until the ethanol evaporates naturally;

[0062] (4) Sinter the material obtained in the previous step at 500°C to 600°C for 4 to 6 hours to obtain modified LiNi 0.6 Mn 0.4 O2 positive electrode material, denoted as Al-NM64.

[0063] Comparative Example 3: (modified with magnesium nitrate)

[0064] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0065] (1) Commercially available Ni 0.6 Mn 0.4 The (OH)2 precursor and battery-grade lithium carbonate were mixed evenly in a molar ratio of 2:1.05 and ground for half an hour;

[0066] (2) The ground material is sintered at 500°C to 850°C for 10 to 20 hours to obtain LiNi 0.6 Mn 0.4 O2;

[0067] (3) Using anhydrous ethanol as the solvent, polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and magnesium nitrate are mixed in a mass ratio of 2:1:0.032, and stirred until the ethanol evaporates naturally;

[0068] (4) Sinter the material obtained in the previous step at 500°C to 600°C for 3 to 7 hours to obtain modified LiNi 0.6 Mn 0.4 O2 positive electrode material, denoted as Mg-NM64.

[0069] Comparative Example 4: (modified with zirconium nitrate)

[0070] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0071] (1) Commercially available Ni 0.6 Mn 0.4 The (OH)2 precursor and battery-grade lithium carbonate were mixed evenly in a molar ratio of 2:1.05 and ground for half an hour;

[0072] (2) The ground material is sintered at 500°C to 850°C for 10 to 20 hours to obtain LiNi 0.6 Mn 0.4 O2;

[0073] (3) Using anhydrous ethanol as the solvent, polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and zirconium nitrate are mixed in a mass ratio of 2:1:0.017, and stirred until the ethanol evaporates naturally;

[0074] (4) Sinter the material obtained in the previous step at 500°C to 600°C for 3 to 7 hours to obtain modified LiNi 0.6 Mn 0.4 O2 positive electrode material, denoted as Zr-NM64.

[0075] Comparative Example 5: (Modification with cadmium nitrate)

[0076] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0077] (1) Commercially available Ni 0.6 Mn 0.4 The (OH)2 precursor and battery-grade lithium carbonate were mixed evenly in a molar ratio of 2:1.05 and ground for half an hour;

[0078] (2) The ground material was sintered at 500℃ for 5h and 850℃ for 15h to obtain LiNi 0.6 Mn 0.4 O2;

[0079] (3) Using anhydrous ethanol as solvent, polyvinyl pyrrolidone (molecular weight 40000), LiNi 0.6 Mn 0.4 O2 and cadmium nitrate are mixed in a mass ratio of 2:1:0.012, and stirred until the ethanol evaporates naturally;

[0080] (4) Sinter the material obtained in the previous step at 500℃~600℃ for 5h to obtain modified LiNi 0.6 Mn 0.4 O2 positive electrode material, denoted as Cd-NM64.

[0081] Comparative Example 6: (Co content is too low)

[0082] The difference between Comparative Example 6 and Example 1 is that polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and cobalt nitrate are mixed in a mass ratio of 2:1:0.003, and the rest is the same as in Example 1.

[0083] Comparative Example 7: (Co content is too high)

[0084] The difference between Comparative Example 7 and Example 1 is that polyvinyl pyrrolidone (PVP, molecular weight 40000-100000), LiNi 0.6 Mn 0.4 O2 and cobalt nitrate are mixed in a mass ratio of 2:1:0.04, and the rest is the same as in Example 1.

[0085] Comparative Example 8: (modified sintering temperature is 700°C)

[0086] The difference between Comparative Example 6 and Example 1 is that the sintering temperature in step (4) is 700° C., and the rest is the same as Example 1.

[0087] Comparative Example 9: (modified sintering temperature is 400°C)

[0088] The difference between Comparative Example 6 and Example 1 is that the sintering temperature in step (4) is 400° C., and the rest is the same as Example 1.

[0089] The positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-9 were mixed evenly with acetylene black and PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1, applied to aluminum foil, and used as the positive electrode after drying. The lithium sheet was used as the negative electrode and assembled into button batteries using 1.2M LiPF6 solution (the solvent was ethylene carbonate and ethyl methyl carbonate, with a volume ratio of 3:7).

[0090] The battery assembled with the positive electrode material prepared in Example 1 and the battery assembled with NM64 and NCM622 were charged with 180 mA g at a voltage window of 2.7 to 4.5 V. -1 (1C) current for cycle testing, the results are as follows Figure 1 As shown. Figure 1 It can be seen that after 130 cycles, the capacity of the commercial NCM622 cathode material has significantly decayed, while the capacity of LiNi 0.6 Mn 0.4 The capacity of O2 (NM64) and the surface-modified material (Co-NM64) obtained in Example 1 is almost unchanged. However, since the polarization resistance of the modified material is significantly reduced, Co-NM64 has a higher capacity and is more suitable for practical applications.

[0091] The battery assembled with the positive electrode materials prepared from NM64, Example 1 and Comparative Examples 1-5 was charged with 180 mA g at a voltage window of 2.7 to 4.3 V. -1 (1C) current is cycled, and the results are as follows Figure 2 As shown. Figure 2 It can be seen that only the battery made of the positive electrode material modified by cobalt element can maintain the LiNi 0.6 Mn 0.4 The stability of O2 (NM64) has significantly improved the discharge capacity. Although the capacity of the battery modified with cadmium has been improved, the cycle stability has been significantly reduced. The overall performance of the battery modified with other elements has even decreased compared to the unmodified NM64. Therefore, the positive electrode material prepared by surface modification of cobalt nitrate can significantly improve the LiNi 0.6 Mn 0.4 Electrochemical properties of O2(NM64).

[0092] The performance of the batteries assembled by using the positive electrode materials prepared in Example 1 and Comparative Examples 6-9 was tested. The discharge capacity of the batteries assembled in Comparative Examples 6-9 was not as good as that of Example 1 of the present invention. 0.6 Mn 0.4 When the mass ratio of O2 to cobalt nitrate is 1:0.005-0.03, it can effectively improve the performance of LiNi 0.6 Mn 0.4 O2(NM64) surface. Because the mass ratio of cobalt is too low to 0.6 Mn 0.4 O2(NM64) is effectively modified, and too high a mass ratio is not conducive to the formation of a good lithium ion conductor LiNi 1-x-y Co x Mn yO2, thus hindering the transmission of lithium ions, increasing polarization, and reducing battery capacity; at the same time, the cost will increase due to the large amount of cobalt used. 0.6 Mn 0.4 O2 re-sintering, cobalt nitrate is converted to cobalt tetroxide, and the original cobalt tetroxide coating is converted to gradient distribution of LiNi 1-x-y Co x Mn y O2 not only improves the LiNi 0.6 Mn 0.4 The conductivity of O2 also makes the surface modification layer and LiNi 0.6 Mn 0.4 O2 is more compatible and has the advantages of both modification and doping. Because when the sintering temperature is too low, cobalt tetroxide is not enough to fully react with Li to form a gradient distribution of LiNi 1-x-y Co x Mn y O2, the conductivity will also decrease, and even polyvinyl pyrrolidone cannot be completely decomposed; and if the sintering temperature is too high, the internal defects of the material will increase significantly, and the performance will be significantly reduced. The results obtained in Example 2 and Example 3 are the same as those in Example 1, and will not be repeated here.

[0093] The lithium-ion battery positive electrode material particles prepared in Example 1 were cut open using a focused ion beam (FIB), and slices were taken from the surface to the inside. Through the elemental analysis function of a transmission electron microscope (TEM), it can be concluded that the cobalt element is distributed in a gradient. Figure 3(a) is a slice diagram taken from the material particles using a focused ion beam (FIB) of the positive electrode material particles prepared in Example 1, corresponding to the surface and the inside of the material from top to bottom. Figure 3(b) is a Co element distribution diagram inside the Co-NM64 grains corresponding to Figure 3(a). The denser the points in the figure, the higher the cobalt content. It can be seen from Figures 3(a) and 3(b) that the cobalt content gradually decreases from the surface to the inside, showing a gradient distribution.

[0094] Figure 4 This is a curve showing the content change of the three elements of nickel, cobalt and manganese from the surface to the interior of the Co-NM64 grain, a positive electrode material for lithium-ion batteries, prepared in Example 1. As can be seen from the figure, the cobalt element gradually decreases from the surface to the interior, and the nickel element and the manganese element are distributed in a stoichiometric ratio.

[0095] In summary, the present invention adopts a relatively simple preparation method to prepare low-cost cobalt-free positive electrode material LiNi 0.6 Mn 0.4 O2 is used to modify the surface of the cathode material, and the electrochemical performance of the resulting cathode material is greatly improved, which has great practical value and broad market prospects. In particular, during the high-temperature sintering process, cobalt nitrate is converted into cobalt tetroxide, which can react with LiNi0.6 Mn 0.4 The residual lithium source on the O2 surface reacts with LiNi 0.6 Mn 0.4 O2 reconstructs the surface of LiNi 0.6 Mn 0.4 The O2 crystal surface is distributed in a gradient within a range of 200 nm from the inside to the surface of the crystal. In this way, the surface of the modified material (abbreviated as Co-NM64, i.e., the positive electrode material of the lithium ion battery prepared by the present invention) becomes LiNi 1-x-y Co x Mn y O2. Because a large part of the battery resistance comes from the interface, reducing the interface resistance can significantly reduce the polarization of the battery, thereby increasing the battery capacity. 0.6 Mn 0.4 The residual lithium source of O2 (which can hinder the transmission of lithium ions) is consumed, and the cobalt element has good conductivity. Therefore, the surface conductivity of the modified material is greatly improved, the resistance is significantly reduced, and the capacity is greatly improved.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: The following steps are involved: Step 1: Ni 0.6 Mn 0.4 The (OH)2 precursor is mixed with lithium carbonate and then ground and sintered to obtain LiNi 0.6 Mn 0.4 O2; Step 2: Using anhydrous ethanol as solvent, polyvinyl pyrrolidone and the LiNi prepared in step 1 are reacted with 0.6 Mn 0.4 Mix O2 and cobalt nitrate and stir until the ethanol evaporates naturally; Step 3: Sinter the material obtained in step 2 at 500 ℃ ~ 600 ℃ for 3 ~ 7 h to obtain surface-modified LiNi 0.6 Mn 0.4 O2, the lithium ion battery positive electrode material is obtained; during the sintering process of step three, cobalt nitrate is converted into cobalt tetroxide, and cobalt tetroxide reacts with the residual lithium source on the surface that hinders the transmission of lithium ions, and LiNi 0.6 Mn 0.4 The surface of O2 is reconstructed so that the Co element is on the LiN i0.6 Mn 0.4 The O2 grain surface to the inner 200 nm range is gradient distribution, and the original cobalt oxide coating layer is transformed into a gradient distribution of LiNi 1-x-y Co x Mn y O2, where 0< x <1, 0< y <1, and x decreases from the surface to the inside; Wherein, in step 2, polyvinyl pyrrolidone and LiNi prepared in step 1 0.6 Mn 0.4 The mass ratio of O2 and cobalt nitrate is 2:1:0.005-0.

03.

2. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step 1, Ni 0.6 Mn 0.4 The molar ratio of (OH)2 precursor to lithium carbonate is 2:1.

05.

3. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step 1, the sintering temperature is 500°C~850°C, and the sintering time is 10~20 h.

4. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step 2, the molecular weight of polyvinyl pyrrolidone is 40,000-100,000.

5. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step 2, polyvinyl pyrrolidone and LiNi prepared in step 1 0.6 Mn 0.4 The mass ratio of O2 and cobalt nitrate is 2:1:0.

018.

6. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step 2, the amount of anhydrous ethanol used is 80-120 times the mass of polyvinyl pyrrolidone.

7. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: The sintering in step 1 and step 3 is performed in an air atmosphere.

Citation Information

Patent Citations

  • Composite lithium ion anode material based on lithium-nickel-cobalt-manganese oxide and preparation method thereof

    CN103000877A

  • Composite coating modified high-nickel NCA positive electrode material and preparation method thereof

    CN113363492A